2017
DOI: 10.1111/trf.14456
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effect of preoperative intravenous iron therapy in colorectal cancer patients with anemia: results of a cohort study

Abstract: Implementation of IV iron therapy in anemic colorectal cancer patients leads to a distinct increase of preoperative Hb level. IV iron therapy is most effective in patients presenting with more severe anemia, and with higher transferrin and lower ferritin levels, markers for an absolute iron deficiency (ID), compared to functional ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
4
38
2
Order By: Relevance
“…Fewer anaemic patients were found to require red cell transfusion after treatment with iron . Since then, more studies have been published supporting these conclusions . No clear differences in other outcomes have been found so far.…”
Section: Why?mentioning
confidence: 88%
See 1 more Smart Citation
“…Fewer anaemic patients were found to require red cell transfusion after treatment with iron . Since then, more studies have been published supporting these conclusions . No clear differences in other outcomes have been found so far.…”
Section: Why?mentioning
confidence: 88%
“…Several studies investigating the effect of treatment of pre‐operative anaemia have been published showing an increase in pre‐operative haemoglobin after i.v. iron treatment . To date, no studies have been published investigating treatment of pre‐operative anaemia on clinical outcomes in this group of patients.…”
Section: Who?mentioning
confidence: 99%
“…2 Numerous studies show the effectiveness of IV iron infusions in patients with anemia. 3,10 However, few studies examine the response to iron infusions in patients with advanced CKD before a major surgery. Our case demonstrates that IV iron and erythropoietin can successfully increase the Hg of a patient with severe anemia and advanced CKD before a major surgery with expected blood loss, and eliminate the need for allogeneic blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis of previous studies investigating ingested iron as treatment of anemia identified it as potentially detrimental and hazardous for human colorectal cancer risk (87)(88)(89). Recent studies demonstrated that compared with oral iron, intravenous iron therapy is more effective in anemic patients with colorectal cancer with higher Tf and lower ferritin levels (90,91).…”
Section: Iron and Various Cancersmentioning
confidence: 99%